Proximity-induced anomalous topological superconductivity in an antiferromagnetic honeycomb-lattice - Fenghua Qi; Yuanyuan Xiang; Jie Cao; Guojun Jin (New Journal of Physics)
Topological superconductivity, generated in an engineered system with the proximity effect from an s-wave superconductor, usually requires the original sample to be a topological insulator. In this study, we propose a novel form of topological superconductivity in a honeycomb lattice arising from both antiferromagnetism (AFM) and s-wave superconductivity. Eventhough the honeycomb lattice with AFM is a normal insulator, the inherent topology of such a system is nontrivial. The topology of the system is determined by the relative values of the s-wave pairing potential and antiferromagnetic order. Notably, there are no chiral edge states at the open boundary if the engineered system is uniform everywhere, whether topologically trivial or not. However, when two parts with different topologies are brought together, two chiral edge states emerge at the topological phase boundary in the middle of the material. This challenges the bulk-edge correspondence observed in conventional topological materials. These chiral edge states are protected by valley symmetry and, owing to their Majorana fermion nature, can contribute to a half-integer quantized conductance.